Analysis of the Song Form and Meaning of the Lyrics of the Song "Nganjuk Nyawiji" by Sony Jatmiko: the background to the creation of the song "nganjuk nyawiji", the form of the song and the meaning of the lyrics of the song "nganjuk nyawiji" - Pratama, Annisa Kusuma (Solah, 2025)
This study aims to describe the form of the song and the meaning of the lyrics of the song "Nganjuk Nyawiji. The song "Nganjuk Nyawiji is a song from Nganjuk Regency which is the work of Sony Jatmiko S.Pd. This study focuses on the song "Nganjuk Nyawiji. The approach used is a qualitative approach. In this study, the research methods used include interviews, documentation, using triangulation of sources and techniques. The results of the study indicate that the song "Nganjuk Nyawiji has a simple melody and lyrics pattern that is easy to sing. Described in the form of a melody score. The lyrics contained in this song have deep meaning.